Strategies and Challenges in English to Chinese Translation of Selected Song Lyrics - Amini, Mansour; Ooi, Faith Fang Xi; Choo, Sue Anne Xuan-En; Saffari, Narges; Lee, Kam-Fong; Ravindran, Latha (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
The translation of song lyrics is challenging for translators primarily due to the intricate poetic and musical elements, which often compel them to employ specific strategies for effective translation. This study was an attempt to investigate the translation strategies in selected translated movie song lyrics and explore the challenges in translating the lyrics. In this qualitative study, the songs were purposefully selected from “Mulan” (1998) and “Aladdin” (2019) movies. Low’s (2013) translation strategies were applied during the process of translation. The “Translation” (transfer of material with a reasonably high degree of semantic fidelity), and “Replacement” (a re-creation of text by only preserving the music element) strategies were found as the common strategies in the translation of song lyrics. The use of a replacement strategy could be due to technical difficulties in translating songs, such as the constraint of rhythm, hence a total replacement of meanings to match the rhythm of the song. A significant challenge in translating song lyrics from English to Chinese was in translating the concept of face-saving, which is an eminent process in social interactions in Chinese culture. It was concluded that the use of a translation strategy depended on the lyrics, translators’ creativity, melody, rhyme, and the differences between the languages and cultures, while the “skopos”, i.e., the correspondence of aim/purpose in the source and target cultures should play the key role.